2009
DOI: 10.2147/ndt.s3896
|View full text |Cite
|
Sign up to set email alerts
|

Atomoxetine for the treatment of attention-deficit/hyperactivity disorder in children and adolescents: a review

Abstract: Objective: This review examines and summarizes the pharmacodynamic and pharmacokinetic properties, short-and longer-term effi cacy, the moderating effect of comorbid disorders, as well as short-and long-term safety and tolerability of atomoxetine for the treatment of pediatric attention-defi cit/hyperactivity disorder (ADHD). Methods: A systematic literature search was performed to review the extant literature on articles pertaining to the pharmacological treatment with atomoxetine in pediatric and/or adolesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 64 publications
0
17
0
Order By: Relevance
“…Indeed, a meta-analysis of pooled data from ATX studies ( N = 601) indicated that the response to ATX continued to grow for as long as 12 weeks, although most of the improvement occurred during the first 4 weeks and any subsequent further improvement occurred in conjunction with increasing mean ATX dose [ 33 ]. There is also evidence to suggest that higher doses of ATX than used in the present study and recommended in the product’s prescribing information (up to 1.8 mg/kg) may result in higher levels of efficacy of ATX [ 34 , 35 ]. In addition, there is some evidence that ATX is more effective when administered twice daily than once daily, as used in the present study [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a meta-analysis of pooled data from ATX studies ( N = 601) indicated that the response to ATX continued to grow for as long as 12 weeks, although most of the improvement occurred during the first 4 weeks and any subsequent further improvement occurred in conjunction with increasing mean ATX dose [ 33 ]. There is also evidence to suggest that higher doses of ATX than used in the present study and recommended in the product’s prescribing information (up to 1.8 mg/kg) may result in higher levels of efficacy of ATX [ 34 , 35 ]. In addition, there is some evidence that ATX is more effective when administered twice daily than once daily, as used in the present study [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with findings in studies of Caucasian and non-Caucasian pediatric patients 7 , 11 - 13 , 15 , 17 , 24 , 26 and may be expected given the increases in noradrenergic tone observed with atomoxetine. 27 …”
Section: Discussionmentioning
confidence: 99%
“…As noted in a recent review by Hammerness and colleagues, “serious cardiovascular side effects have not been noted in trials with therapeutic doses of atomoxetine” [ 4 ]. Usually, the increase in heart rate was estimated to be between 5 and 9 beats.…”
Section: Discussionmentioning
confidence: 99%
“…Classically, stimulants have been used in the treatment of this condition [ 3 ]. Atomoxetine (Strattera; Eli Lilly and Company) is a selective norepinephrine reuptake inhibitor (SNRI), one of the first medications in the nonstimulant class of medications that has been approved by the FDA for the treatment of attention deficit hyperactivity disorder [ 4 ]. “Atomoxetine is a phenoxypropylamine derivative and is structurally related to the antidepressant fluoxetine” [ 5 ].…”
Section: Introductionmentioning
confidence: 99%